PENINGAKATAN KEBERHASILAN MENYUSUI EKSKLUSIF IBU PRIMIPARA MELALUI MODUL MENYUSUI SECARA HOLISTIK DI WILAYAH KAMPUNG SUKAMAJU PURWAKARTA - Tegar Dian Setiawati, Yeni; Nur Allipah , Putri (CV. Publikasi Indonesia, 2025)
Successful exclusive breastfeeding remains a challenge, especially for primiparous mothers with limited experience and information. A holistic breastfeeding module was developed to provide comprehensive education covering physical, psychological, and social aspects. This study aimed to evaluate the effectiveness of the holistic breastfeeding module in improving exclusive breastfeeding success among primiparous mothers in Sukamaju Village, Purwakarta. The study used a quasi-experimental method with a pretest-posttest design on 60 primiparous mothers. Data were collected using a breastfeeding knowledge and attitude questionnaire, exclusive breastfeeding records, and in-depth interviews. Results showed a 45% increase in breastfeeding knowledge, a 35% increase in positive attitudes, and an increase in exclusive breastfeeding success from 50% to 78% after the intervention. Conclusion: The holistic breastfeeding module effectively improves exclusive breastfeeding success among primiparous mothers.